Food habits among adolescents in the Colombo District - Samaranayake, T.S.P (My University, 2007)
Five focus group discussions were carried out with mothers of adolescents andm based on the data gathered, a questionnaire was formulated to use as the study instrument. Eight hundred ( 600 urban, 200 rural) adolescents from grade 10 classes were included in the study. Of the six hundredm 525 were from government schools and 75m from a private international school. A pre-tested self administered questionnaire was used to collect the data and the analysis was done using SPSS and EPi-Info packages. School canteens were visited and the food avalilability and the most demanded food items were also recorded by the investigator. Mean age of the sample was 14.6 years ( range 13.3-16.9) years with a closer representation of males and females. Most of them were Sinhalese Buddihists. As expected, the student from higher socioeconomic background followed by the urban astudents. followed by the urban students. The food habits of adolescents in Colombo district seem to be generally satisfacvtory. However, certain undesirable practices have been detected and need to be addressed. Television viewing has a significant association with adolescent food preferences. It is recommended that the family physicians take a leading role in implementing primary prevention programmes as the impact of such programmes would be high in family practices where doctor patient relationshiops are comparativelly stronger